2004
DOI: 10.1021/ol048549g
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses of ω-Hydroxy-α,α-difluoromethylphosphonates by Oxacycle Ring-Opening Reactions

Abstract: [reaction: see text] Oxacycle ring-opening reactions from a non-HCFC-based source of phosphonodifluoromethyl carbanion 1 are reported. This straightforward strategy opens access to a variety of primary and secondary omega-hydroxy-alpha,alpha-difluoromethylphosphonates via one step. The syntheses of a glycerol monophosphate analogue and precursors to nucleoside phosphorylase inhibitors are described using this method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…We assumed that the nucleophilicity of PhSO(NTBS)CF 2 − towards the epoxide was not high enough and that activation of 4 a would be needed to achieve the ring‐opening difluoromethylation reaction. Previously, BF 3 ⋅ Et 2 O has often been used as a Lewis acid to activate epoxides in their reactions with carbanions 6b. 8, 14 Two traditional procedures have been applied: 1) adding the epoxide to mixtures of BF 3 ⋅ Et 2 O and carbanions;14 2) adding BF 3 ⋅ Et 2 O immediately after the addition of the epoxide to a solution of the carbanion 6b.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We assumed that the nucleophilicity of PhSO(NTBS)CF 2 − towards the epoxide was not high enough and that activation of 4 a would be needed to achieve the ring‐opening difluoromethylation reaction. Previously, BF 3 ⋅ Et 2 O has often been used as a Lewis acid to activate epoxides in their reactions with carbanions 6b. 8, 14 Two traditional procedures have been applied: 1) adding the epoxide to mixtures of BF 3 ⋅ Et 2 O and carbanions;14 2) adding BF 3 ⋅ Et 2 O immediately after the addition of the epoxide to a solution of the carbanion 6b.…”
Section: Resultsmentioning
confidence: 99%
“…8, 14 Two traditional procedures have been applied: 1) adding the epoxide to mixtures of BF 3 ⋅ Et 2 O and carbanions;14 2) adding BF 3 ⋅ Et 2 O immediately after the addition of the epoxide to a solution of the carbanion 6b. 8 As discussed by Ganem et al.,14 these successful reactions would indicate that combinations of such carbanions and BF 3 ⋅ Et 2 O are reasonably stable under certain reaction conditions, allowing them to react independently as potent nucleophile and strong Lewis acid, respectively 6b. 8, 14 However, in the case of sulfoximine 2 , compound 5 was not obtained by using either of these two procedures (Scheme b, c).…”
Section: Resultsmentioning
confidence: 99%
“…Synthesis of an enantiomerically pure amino alcohol moiety could be achieved by selective ring opening of chiral aziridines with various nucleophiles (Hu, 2004). Oxirane ring opening by α,α-difluoromethylene-phosphonate anion to furnish γ-hydroxy-α,α-difluoromethylenephosphonates has been reported (Ozouf et al, 2004; Pajkert et al, 2008); however, aziridine ring opening with the same anion has not been reported to date. Thus, we speculated that the reaction of chiral aziridine with α,α-difluoromethylene diethylphosphonate anion might provide facile access to the desired non-hydrolyzable phosphoserine core structure.…”
Section: Resultsmentioning
confidence: 99%
“…Lequeux and co‐workers [163] and later Koroniak, Röschenthaler, and co‐workers [164,165] reported regiocontrolled ring‐opening of epoxides with LiCF 2 P(O)(OEt) 2 in the presence of Lewis acids as a route toward α,α‐difluoro‐γ‐hydroxyphosphonates 102 (Scheme 43). Alternatively, cyclic sulfates of 1,2‐diols could be used as substrates providing products 102 in even better yields and excellent regioselectivity [166,167] .…”
Section: Synthetic Methodsmentioning
confidence: 99%